Evaluasi Penerapan Good Farming Practice dan Implikasinya terhadap Kelayakan Usaha Pemeliharaan Sapi Potong pada Peternakan Rakyat - Hana Nur Eritrina; Febby Ardilia; Sunarto Sunarto (Universitas Galuh, 2026)
Beef cattle are cattle specifically raised for their meat, characterized by rapid growth and a large body structure. Efforts to optimally improve the quality and quantity of beef require good beef cattle farming practices, also known as Good Farming Practice (GFP). The objectives of this research were to describe the implementation of Good Farming Practice (GFP), analyze the feasibility of beef cattle farming in the Banjar Tani 2 Livestock Group, and obtain material for developing a beef cattle fattening Business Plan based on GFP. The research method used was descriptive quantitative with cross-tabulation (Crosstab). The study results indicated that the implementation of Good Farming Practices (GFP), assessed from 30 farmers in the Banjar Tani 2 Livestock Group, yielded a score of 772.8 with a